2011
DOI: 10.1021/nn103265h
|View full text |Cite
|
Sign up to set email alerts
|

The Enzymatic Oxidation of Graphene Oxide

Abstract: Two-dimensional graphitic carbon is a new material with many emerging applications, and studying its chemical properties is an important goal. Here, we reported a new phenomenon -the enzymatic oxidation of a single layer of graphitic carbon by horseradish peroxidase (HRP). In the presence of low concentrations of hydrogen peroxide (~40 µM), HRP catalyzed the oxidation of graphene oxide, which resulted in the formation of holes on its basal plane. During the same period of analysis, HRP failed to oxidize chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
346
3
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 365 publications
(369 citation statements)
references
References 56 publications
15
346
3
5
Order By: Relevance
“…Similar observations were demonstrated in other CNM degradation studies. 17 Later on for GO, the I D /I G ratio began to decrease noticeably (Day 3) and the spectra started to lose the characteristic Raman signature of GO (Days 5 and 7). This was expected and is confirmation of degradation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar observations were demonstrated in other CNM degradation studies. 17 Later on for GO, the I D /I G ratio began to decrease noticeably (Day 3) and the spectra started to lose the characteristic Raman signature of GO (Days 5 and 7). This was expected and is confirmation of degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding degradability, several studies have investigated and demonstrated the degradation of CNMs including graphene using enzymes, such as lignin peroxidase 16 or horseradish peroxidase. 17 Chemical strategies such as Fenton-based chemistry have also been tested. 18 However, studies directly comparing the degradation kinetics of CNMs of different geometries in an oxidative environment are lacking.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The adsorption of the protein (enzyme) molecules on graphene and GO, in turn, may improve their biocompatibilities or accelerate their chemical process or biodegradation. Kotchey et al studied systematically the enzymatic oxidation of GO and CRGO by HRP in the presence of hydrogen peroxide [133] . As shown in Figures 15 and 16 , with electron microscopy, it was found that the HRP could catalyze the oxidation of GO, but not the CRGO.…”
Section: Improvement Of the Biocompatibility And Biodegradation Of Gomentioning
confidence: 99%